Indiani, tabacco e schiavi: alcune riflessioni sugli esordi dellacolonizzazione inglese in Virginia (sec. XVII) - Carbone, Fausto Ermete (Études sur la Région Méditerranéenne, 2017)
The founding of Jamestown is the first experiment of permanent colonization undertaken by England in North America. The administration of this possession was very complex during the early stages. To overcome the difficulties, the British tried to follow the Spanish colonial model, which was successful in Central and South. To analyze the evolution of Virginia colony, as this article aims to do, it may be useful to understand on what grounds was built the British colonial model. A model that will win the competition with each rival state during the eighteenth century.